Overweight and obesity among school-going children of Lucknow city - Rajaat Vohra; Pankaj Bhardwaj; Jyoti P Srivastava; Shekhar Srivastava; Anusha Vohra (Wolters Kluwer Medknow Publications, 2011)
Background: Childhood obesity is increasingly being observed with changing lifestyles of families. The magnitude of overweight ranges from 9% to 27.5% and obesity ranges from 1% to 12.9% among Indian children. Objectives: The present study was undertaken to study the magnitude of overweight/obesity and its determinants among children in Lucknow city. Materials and Methods: A list of government and private school was procured from Office of Basic Shiksha Adhikari. Three government and three private schools were selected by Simple Random Sampling. Students of 5th to 12th grades available at the time of study were included as study unit. Predesigned and pretested questionnaire was used to elicit the information on family characteristics and individual characteristics. Height and weight were measured and BMI was calculated. Children with BMI of 25 and above were considered overweight and children with BMI more than 30 were considered obese. Results: Overweight and obesity was found to be 4.17% and 0.73%, respectively; they together constitute 4.91% for overweight/obesity. The study revealed that the important correlates of overweight/obesity were father's education, father's occupation, class, children playing outdoor games for less than 30 min, and those consuming fast foods. Conclusions : Children of higher classes (above 8th standard) belonging to higher socioeconomic group with less outdoor activities and consuming fast foods were more predisposed to overweight/obesity. As a preventive strategy, there is a need to apply health and nutritional education programs for inculcating healthy life styles, and incorporating more outdoor activities in Physical Education Department of school curriculum.